2011
DOI: 10.1093/jnci/djr299
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Rates Among Early-Stage Hormone Receptor-Positive Breast Cancer Patients: A Population-Based Cohort Study in Denmark

Abstract: A small subgroup of breast cancer patients who were 60 years or older and had hormone-responsive early-stage tumors up to 10 mm, and received no systemic adjuvant therapy, were not at increased risk of mortality compared with women in this age-group in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 31 publications
1
35
0
2
Order By: Relevance
“…Women with early breast cancer are increasingly being exposed to adjuvant systemic therapies, which can safely be omitted in only a small subgroup of node negative patients aged 60 or older with estrogen receptor (ER) positive, HER2 negative, grade I tumors of 10 mm or less [11]. Endocrine treatment is the key component of the adjuvant therapy in patients with ER positive tumors and its duration has gradually been extended [12][13][14].…”
mentioning
confidence: 99%
“…Women with early breast cancer are increasingly being exposed to adjuvant systemic therapies, which can safely be omitted in only a small subgroup of node negative patients aged 60 or older with estrogen receptor (ER) positive, HER2 negative, grade I tumors of 10 mm or less [11]. Endocrine treatment is the key component of the adjuvant therapy in patients with ER positive tumors and its duration has gradually been extended [12][13][14].…”
mentioning
confidence: 99%
“…These results also indicated that ∼60% of patients may be overexposed to hormonal therapy toxicity and incur costs to the health care system with little or no clinical benefit under the traditional clinical‐pathological decision‐making approach. Another study showed that adjuvant hormonal therapy can be omitted for a small group of early stage of ER+ patients . Identifying these low risk patients is of clinical importance to spare patients from overtreatment and reduce the burden on the health care system.…”
Section: Discussionmentioning
confidence: 99%
“…And more recently, by combining a number of factors, data from large cohorts of patients entering different DBCG programs have been utilized to better identify patients eligible for systemic therapy 14,15…”
Section: Researchmentioning
confidence: 99%